STUDY OF MOBILE APPLICATION USE ON DETERMINING FUNCTIONAL CONDITIONS OF ROAD PAVEMENT - Wiliyanda Nasution, Derry
The amount of costs which needed to procure the measurement equipment of road condition make these equipment did not available to every regions of Indonesia. To overcome the problem of the availability of these equipment, road agency usually conducts visual survey in determining the conditions of road pavement. In line with technological developments, many inovation had been made that functional conditions of road pavement can be determined by smartphone using road roughness measurement. RoadroidTM is a mobile application that can be used in these measurements on IRI units. On this research there will be studied about how the validity of road condition and roughness data quality which obtained by using Roadroid. study about the comparation between Pavement conditioan according to Roadroid’s IRI and the pavement conditi according to PCI method. Because this application is planned to be used by regional road authorities, this research was conducted on the city road segment in Bandung City, precisely the Jalan Peta with the total length of the 1800m case study area. This research was conducted through a direct survey at the location of the case study with three speed variations such as of 20-40km/h, 40-60km/h, and 60-80km/h and repeated three times. As a comparison in this study also measured the condition of the road visually precisely using the PCI method. Based on the analysis conducted in this study, the best quality data obtained from speed of 20-40km/h with repetition errors that occurred in most Roadroid IRI samples with speeds of 20-40km/h <20% for 20m segmentation, <12% for 50m segmentation, and <11% for 100m segmentation. In terms of speed, the higher the speed of the survey carried out higher IRI.From the analysis, it can be seen that the pavement conditions based on Roadroid IRI of 20-40km/h has more same reading with PCI pavement conditions. In terms of segmentation, the longer the segmentation interval used the greater the correlation between IRI Roadroid and PCI pavement conditions. this become more clearly with the results of the association test where the correlation coefficient obtained according to the Spearman Rank test is 0.774 and 0.737 for the Kendall Rank test for 100m segmetation.